Improving English Descriptive Writing Skill Through Brainstorming Technique - Masitah, Siti; Marita, Yosi; Rakhmanina, Lisa; Melati, Melati; Firdaus, Muhammad Alif (Edu-Ling: Journal of English Education and Linguistics, 2024)
Generally, the purpose of  this research was to improve the writing learning process, namely how to implement English descriptive writing teaching using brainstorming techniques in the English Language Education Study Program, Prof. University. Dr. Hazairin S.H involving lecturers and students. Furthermore, the specific technique of this research aims to describe the use of brainstorming in writing descriptive English teaching and to found out the results of descriptive writing produced by students after using this brainstorming technique. This research was mixed research (mixed methods) with an Action Research design, where qualitative data mining will first be carried out to explore in depth how Brainstorming techniques can be applied in improving students' descriptive writing skills. Then proceed with quantitative data collection. The research results showed that there was an increase in students' English descriptive writing skills. This can be seen from the increase in scores from the pre test, Post test cycle I, and post test cycle II. The students' average score increased from 68.54 in the first cycle post test to 73.00 in the second cycle post test. From these results it can be concluded that the brainstorming technique is effective in improving students' English descriptive writing skills.